Development of mapped stress‐field boundary conditions based on a Hill‐type muscle model. (7th April 2014) - Cardiff, P.; Karač, A.; FitzPatrick, D.; Flavin, R.; Ivanković, A.
SUMMARY Forces generated in the muscles and tendons actuate the movement of the skeleton. Accurate estimation and application of these musculotendon forces in a continuum model is not a trivial matter. Frequently, musculotendon attachments are approximated as point forces; however, accurate estimation of local mechanics requires a more realistic application of musculotendon forces. This paper describes the development of mapped Hill‐type muscle models as boundary conditions for a finite volume model of the hip joint, where the calculated muscle fibres map continuously between attachment sites. The applied muscle forces are calculated using active Hill‐type models, where input electromyography signals are determined from gait analysis. Realistic muscle attachment sites are determined directly from tomography images. The mapped muscle boundary conditions, implemented in a finite volume structural OpenFOAM (ESI‐OpenCFD, Bracknell, UK) solver, are employed to simulate the mid‐stance phase of gait using a patient‐specific natural hip joint, and a comparison is performed with the standard point load muscle approach. It is concluded that physiological joint loading is not accurately represented by simplistic muscle point loading conditions; however, when contact pressures are of sole interest, simplifying assumptions with regard to muscular forces may be valid. Copyright © 2014 John Wiley & Sons, Ltd.